Extraction of Phytochemical Compounds from Pressed-Palm Fiber Using Water and Pressurize Carbon Dioxide - Putu Adhitya Dita Putra; Bella Putri Novitasari; Sugeng Winardi; Tantular Nurtono; Kusdianto Kusdianto; Siti Machmudah (Seminar Nasional Teknik Kimia Kejuangan, 2017)
Sub-critical extraction of palm oil from pressed palm fiber using water and preassured carbon dioxide solventwas conducted via the dynamic mode to investigate the ability of water and CO2 to extract α-tocopherol, β-carotene, and phenolic compounds. The yield of palm oil and the solubility of α-tocopherol, β-carotene, andphenolic compounds were investigated at 120; 140; 160; and 180oC and pressure range from 30–100 bar. Theextracted oil was analysed α-tocopherol, β-carotene, and phenolic compounds content using UV–Visspectrophotometry. The results The temperature increase on the process of extracting hydrothermal on thetemperature (120-180oC) increase yield α-tocopherol .The steady to extract α-tocopherol , an acid palmitateand β-carotene on the temperature 180oc with pressure 10 MPa .From the experiment done get the best resulton the temperature 180oC to pressure 10 MPa with yield α-tocopherol 271,28 mg/g sample (% recovery is73,06%), yield pamitate acid 2,066 mg/g sample (% recovery is 0,55% ), and yield β-carotene 0,008 mg/gsample (% recovery is 0,0021 %) as compared to that achieved through conventional palm oil processingindicates that extraction of α-tocopherol, β-carotene, and phenolic compounds using this methode is viable.